Factors influencing the individual investors of Bangladesh to opt for investment in ṣukūk - Tasruma Sharmeen Chowdhury; S.M. Kalbin Salema (Islamic Economic Studies (IES), 2023)
Purpose - This study aims to identify the factors that influence the willingness of Bangladeshi retail investors to invest in ṣukūk. Design/methodology/approach - The authors surveyed Bangladeshi retail investors using a structured questionnaire to understand their perspectives on potential investment in ṣukūk. The authors considered the behavioral aspects of retail investors and the desired ṣukūk features to analyze the demand side. Factors and regression analyses were performed to identify the persuading factors. Findings - The results indicate that investor awareness is a fundamental factor in potential investments in ṣukūk. Investors perceive the security represented by government and third-party guarantees as a persuasive feature of ṣukūk. The tradability and tenor of ṣukūk also affect the investment intention. Sharī'ah consciousness of the investors also plays a significant role in their investment decisions. Research limitations/implications - One limitation of this study is that it incorporates potential individual investors only, and precludes institutional investors. In the future, there is scope for research to explore the demand factors impacting institutional investors of ṣukūk in Bangladesh. Practical implications - The authors expect that the study will aid policymakers and ṣukūk issuers in crafting strategies to cater to the needs of Bangladeshi retail investors. Originality/value - This study is the earliest research conducted in Bangladesh to determine the factors impacting the willingness of individual investors to make their potential investments in ṣukūk. To the best of the authors' knowledge, no study has analyzed the desired ṣukūk features from the perspective of Bangladeshi retail investors.
Keywords: G1; G11; 330; Bangladeshi investors; Demand; Investment; ṣukūk